Development Of An Instrument For Assessment Of Creative Thinking Skills Based On Collaborative Problem Based Learning - Hidayah, Rusly (International Journal of Educational Research & Social Sciences, 2023)
Learning model Collaborative Problem Based Learning (CPBL) has the potential to improve students' creative thinking skills by providing collaborative learning and students are trained in how to solve problems that are very close to their lives. To find out the students' creative thinking skills, standard, valid, and reliable CPBL- oriented assessment instruments are needed. In connection with the description of the thoughts and research results above, the general objective of this study: to develop an assessment instrument for creative thinking skills and the feasibility of the developed assessment instrument. The validation results show that the creative thinking skills assessment instrument has a score of 3.67-4.00 with a very valid category. The results of the reliability test showed that the instrument for assessing creative thinking skills had a Cronbach's Alpha value of 0.864 in a very strong category.